THE IMPACT OF MODERN INFORMATION PSYCHOLOGICAL THREATS ON YOUTH WORLDVIEWS - Muxiddinova Dilnoza (International Engineering Journal For Research & Development, 2021)
In today's world, where the world has become a single information space, the struggle for ideas is intensifying in various forms. At the same time, in the words of the Head of State, the struggle against anti-idea, anti-ignorance and enlightenment is becoming their main motto in the activities of the media. It is known that every newspaper, magazine, radio, television, the Internet has the power to have different levels of psychological impact on the public consciousness. For example, in newspapers, opinions are conveyed in writing, and when the time comes, through pictures. Information provided in the press can also be read over and over again and used as a source. This is one of the advantages of print media. In this article, Modern Information discusses the impact of psychological threats on young people’s worldview.